POTENSI DAN PENGEMBANGAN KOMODITAS UNGGULAN SEKTOR PERTANIAN DI PROVINSI SUMATERA UTARA - Desi Novita; Mhd. Ilham Riyadh; Mhd. Asaad; Teja Rinanda (JURNAL AGRICA, 2023)
North Sumatra Province is one of the provinces in Indonesia that places the agricultural sector as a sector that makes a major contribution to the formation of GRDP and employment. The agricultural sector contributes to the GDP of 22.04% and employment of 35.43% of the total workforce. This condition is the basis for consideration for the government to develop the agricultural sector through the superior commodity approach. This study aims to determine the direction of development of leading commodities in the agricultural sector in North Sumatra Province. The data used are primary and secondary data obtained through literature studies and interviews with experts/experts and policy makers. The selection of respondents was done intentionally. The data analysis method used is the SLQ and DLQ, ISM, and SWOT analysis methods. The results showed that the main commodities that were prioritized to be developed in North Sumatra Province were red chili, cabbage, tomatoes, eggplant, rubber, durian, salak, rubber and marine fisheries. The criteria for determining areas that are prioritized for developing superior commodities are areas that are included in quadrant I, namely those that show SLQ and DLQ values ​​greater than 1. There are 3 main criteria that affect the development of regional superior commodities, including job creation, increasing competitiveness, and providing contribution to the local economy. The direction of developing superior commodities in North Sumatra Province within the next 5 years is increasing productivity, increasing competitiveness of export-oriented leading commodities, intensification of sustainable agriculture-based agriculture, strengthening agricultural institutional regulations, strengthening supply chains, strengthening farmer competencies and capabilities, and increasing downstreaming of superior commodity products in the agricultural sector.